Autophagic reliance promotes metabolic reprogramming in oncogenic KRAS-driven tumorigenesis. Issue 9 (2nd September 2018) - Lin, H. Helen; Chung, Yiyin; Cheng, Chun-Ting; Ouyang, Ching; Fu, Yong; Kuo, Ching-Ying; Chi, Kevin K.; Sadeghi, Maryam; Chu, Peiguo; Kung, Hsing-Jien; Li, Chien-Feng; Limesand, Kirsten H.; et al.
ABSTRACT: Defects in basal autophagy limit the nutrient supply from recycling of intracellular constituents. Despite our understanding of the prosurvival role of macroautophagy/autophagy, how nutrient deprivation, caused by compromised autophagy, affects oncogenic KRAS-driven tumor progression is poorly understood. Here, we demonstrate that conditional impairment of the autophagy gene Atg5 ( atg5- KO) extends the survival of KRAS G12V -driven tumor-bearing mice by 38%. atg5- KO tumors spread more slowly during late tumorigenesis, despite a faster onset. atg5- KO tumor cells displayed reduced mitochondrial function and increased mitochondrial fragmentation. Metabolite profiles indicated a deficiency in the nonessential amino acid asparagine despite a compensatory overexpression of ASNS (asparagine synthetase), key enzyme for de novo asparagine synthesis. Inhibition of either autophagy or ASNS reduced KRAS G12V -driven tumor cell proliferation, migration, and invasion, which was rescued by asparagine supplementation or knockdown of MFF (mitochondrial fission factor). Finally, these observations were reflected in human cancer-derived data, linking ASNS overexpression with poor clinical outcome in multiple cancers. Together, our data document a widespread yet specific asparagine homeostasis control by autophagy and ASNS, highlighting the previously unrecognized role of autophagy in suppressing the metabolic barriers of low asparagine and excessive mitochondrial fragmentation to permit malignant KRAS-driven tumor progression.